The value of preoperative period to restore motor function of the knee joint during arthroscopic reconstruction of the anterior cruciate ligament - Ніканоров [Oleksiy Nikanorov], Олексій Константинович (Slobozhanskyi Herald of Science and Sport, 2013)
The question of the role of the preoperative period of physical rehabilitation in patients with damage to the anterior cruciate ligament of the knee. The analysis and synthesis of scientific and methodological information on the most typical dysfunctions of the musculoskeletal system in patients as a result of damage to the anterior cruciate ligament, as well as modern means and methods of recovery for injuries capsule and ligaments of the knee. Found that among the domestic and foreign authors there is no consensus on the duration of preoperative period relevant patients. The earliest use of means and methods of physical rehabilitation after anterior cruciate ligament injury can reduce symptoms of post-operative complications and improve motor recovery of damaged limbs.